Approximate Bayesian Implementation and Exact Maxmin Implementation: An Equivalence - Yangwei Song (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2022)
This paper provides a micro-foundation for approximate incentive compatibility using ambiguity aversion. In particular, we propose a novel notion of approximate interim incentive compatibility, approximate local incentive compatibility, and establish an equivalence between approximate local incentive compatibility in a Bayesian environment and exact interim incentive compatibility in the presence of a small degree of ambiguity. We then apply our result to the implementation of efficient allocations. In particular, we identify three economic settings – including ones in which approximately efficient allocations are implementable, ones in which agents are informationally small, and large double auctions – in which efficient allocations are approximately locally implementable when agents are Bayesian. Applying our result to those settings, we conclude that efficient allocations are exactly implementable when agents perceive a small degree of ambiguity.
Keywords: 330; approximate local incentive compatibility; ambiguity aversion; efficiency; informational size; modified VCG mechanism; double auction